Structural aspects of the Mucor bacilliformis proteinase, a new member of the aspartyl-proteinase family - Machalinski, Claudia (2006)
Bovine chymosin is considered the best milk-clotting enzyme for cheese manufacture; however, the thermophilic Mucor pusillus proteinase is also used nowadays. We herein report structural aspects of the aspartyl proteinase from the local mesophilic Mucor bacilliformis strain. Sequence data indicate a high similarity degree to those of other family members. The protein is monomeric, not glycosylated, has two disulfide bridges, and mainly includes beta structure. A molecular model was built by using the Rhizopus chinensis proteinase structure as the template. Sequence analysis and comparison of our model with bovine chymosin and M. pusillus proteinase structures, indicate that the M. bacilliformis proteinase is at a similar evolutionary distance on a sequence level; as regards tertiary structure, the M. bacilliformis proteinase superimposes on the bovine chymosin structure in a fashion similar to that of the M. pusillus proteinase. Overall results suggest that this novel proteinase can be utilized as a good milk-clotting enzyme in the dairy industry.